A Comprehensive Review of the Ethnobotanical Uses, Pharmacological, and Toxicological Profiles of Piper capense L.f. (Piperaceae) - Gabriel Tchuente Kamsu; Eugene Jamot Ndebia (MDPI AG, 2024)
Commonly known as wild pepper, Piper capense (P. capense) is a culinary herb mainly used as a secret in preparation of "Nkui" and "Nah poh" in Bayangam, West Cameroon. However, it also has many interesting pharmacological properties, which is why the people of sub-Saharan Africa so highly prize it for the treatment of multiple human pathologies. This study aimed to highlight the traditional uses, phytochemical composition, biological activities, and toxicological profile of the P. capense plant, to draw the attention of pharmaceutical companies to its enormous potential for the development of future phyto- or pharmaceutical products. Documentary research was meticulously carried out in the Web of Sciences, Scopus, Pubmed/Medline, and Google Scholar databases according to PRISMA 2020 guidelines. The results show that extracts and compounds isolated from Piper capense have interesting anticancer, antibacterial, antimalarial, hypoglycemic, anti-epileptic, and antidepressant activities. Methanolic extracts and essential oils from P. capense exhibit no harmful effects when directly applied to normal human hepatocytes, umbilical cord cells, intestinal cells, and keratinocyte cell lines. Additionally, methanolic extracts administered acutely or subchronically at low doses (≤250 mg/kg body weight) in Wistar rats also demonstrate no adverse effects. In conclusion, given its interesting activities, P. capense is a viable option for developing new antimalarial, anticancer, antibacterial, hypoglycemic, anti-epileptic, and antidepressant drugs. However, many avenues still need to be explored before translation into drugs.